دور التشريع والتنظيم في ضبط وتطوير مهنة المراجعة في الجزائر - لبوز, نوح (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى معرفة دور التشريع والتنظيم في وضع الضوابط والاسس التي تعمل على تطوير مهنة المراجعة وجعلها تتماشى وواقع بيئة الأعمال الجزائرية انطلاقا من الادوات القانونية المتاحة في البيئة القانونية الجزائرية في مجال المراجعة وتوجيهها وفق متطلباتالواقع الاقتصادي للدولة الجزائرية. ولتحقيق هذه الدراسة تم استخدام المنهج الوصفي الاستقرائي من خلال تحليل التشريع والتنظيم اللذان يحكمان ممارسة مهنة المراجعة في الجزائر ابتداء من سنة 2010 الى يومنا هذا. وأبرزت هذه الدراسة أن الالتزام بتطبيق التشريع والتنظيم في بيئة الأعمال الجزائرية، يعطي المراجعة دفعا جديدا من الضبط والتطوير لخدمة الواقع الاقتصادي السائد خلال هذه الفترة. This study aims to know the role of legislation and regulation in setting the controls and foundations that work to develop the audit profession and make it in line with the reality of the Algerian business environment, based on the legal tools available in the Algerian legal environment in the field of auditing and directing it according to the requirements of the economic reality of the Algerian state. To achieve this study, the descriptive inductive approach was used by analyzing the legislation and regulation that govern the practice of the audit profession in Algeria from 2010 to the present day. This study highlighted that the commitment to the application of legislation and regulation in the Algerian business environment gives the review a new impetus of control and development to serve the prevailing economic reality during this period.
The role of the legislation and regulations in controlling and developing the Audit profession in Algeria
مقال
Keywords: تشريع، تنظيم، ضبط، بيئة الأعمال الجزائرية.